Perspektif Public Relations (KajianTentang Marketing PT. Radio Suara Mandala 96,4 FM Banyuwangi) - Abdi Fauji Hadiono (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2017)
Public relation is an overall effort done in a planned and sustainable in order to create and maintain goodwill (goodwill) and mutual understanding between an organization with all its audience. The problem studied in this research is Marketing that uses public relations at PT. Radio Suara Mandala 96.4 Fm Banyuwangi. Using qualitative research methods. In collecting data using interview method, participant observation, and documentation, then the data collected in if and analyzed by using interactive model Miles and Huberman. To test the validity of data is Triangulation Method, Trianggulasi Sumber, Triangulasi Theory. From the results of this study in the know that in PT. Radio Suara Mandala 96.4 FM, marketing using public relations with 3 criteria, including Marketing Strategy (research, forming marketing objectives), Implementation of Marketing Strategy (implements public relations plan) and Evaluation of marketing strategy (evaluating results using public relations)